The plantation of Ulster : ideology and practice - Ó Ciardha, Éamonn; Ó Siochrú, Micheál, 1966- (Studies in early modern Irish history., 2014)
This book is the first major academic study of the Ulster Plantation in over twenty-five years. The pivotal importance of the plantation to the shared histories of Ireland and Britain would be difficult to overstate. It helped secure the English conquest of Ireland, and dramatically transformed Ireland's physical, demographic, socio-economic, political, military, religious and cultural landscapes. Indeed, those legacies are still contested. The divisions between the descendants of the native and settler communities continue to underpin Irish and British politics. As the peace process evolves and the violence of the previous forty years begins to recede into memory, vital space has been created for a timely reappraisal of the plantation process and its role in identity formation within Ulster, Ireland and beyond. This collection of essays by leading scholars in the field on a broad range of historical and literary topics offers an important redress in terms of the previous coverage of the plantations, moving away from an exclusive colonial perspective, to include the native Catholic experience, and in so doing will hopefully stimulate further research into this crucial episode in Irish and British history. -- Back cover.